The Madurese Wedding Traditions (Case Study in Sumberejo Jember) - Shalati, Syadza Fildzah; Nisa, Hikmah Widiatun; Salsabila W, Ajeng Aulia (El-Usrah: Jurnal Hukum Keluarga, 2023)
Marriage traditions are long-standing customs of the union of two individuals that have been passed down through the generations. Each region has its own characteristics and variations of this wedding custom, including the Madurese. The Madurese is an ethnic group with a substantial population in Indonesia, numbering around 7 million people. They originate from Madura Island and the neighboring islands of Gili Raja, Sapudi, Raas, and Kangean. Sumberejo Jember Village is one of the Madurese-inhabited areas. The majority of Madurese adhere to Islam. Sumberejo Village is located within the Ambulu District. Ambulu sub-district is one of the sub-districts located on the southern edge of Jember Regency, 31 kilometers away from the district capital. This study aims to investigate the phenomenon, the influence of the Madurese marriage tradition, and the Islamic legal perspective on marriage. This study employs a qualitative approach and case study research design. The findings of this investigation indicate that: (1) the Madurese wedding tradition exists in Sumberejo Jember. The Madurese wedding tradition in Sumberjo Jember has three positive effects and two negative effects. (3) According to Islam, marriage is among the greatest acts of worship.